2021
DOI: 10.52628/87.3.07
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of head-shaft angle and neck-shaft angle in childhood

Abstract: The current retrospective study investigates the natural evolution of head-shaft angle (HSA) and neck-shaft angle (NSA) in childhood. It is not known if a high HSA in early childhood leads to a high HSA in adulthood. This study aims to characterize the evolution of HSA and compares it with the more commonly known NSA in healthy children. We measured radiographs of 84 different healthy hips of children between 3 and 14.5 years old who underwent at least 2 radiographs of the pelvis, corresponding to 286 measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Non-CP children with high NSA and HSA at age 3 years old showed a continuous decrease in angles (average decrement in NSA, −1.1°/year [95% CI: −1.5 to −0.8°/year]; in HSA, −1.1°/year [95% CI: −1.5 to − 0.7°/year]). [ 21 ] One study comparing the evolution of the HSA in CP and non-CP children showed that the HSA of non-CP children and ambulatory CP children (GMFCS levels II and III) decreased between 2 and 8 years of age. In contrast, the HSA of nonambulatory children with CP (GMFCS levels IV and V) did not show a decrement as they grew over the same period.…”
Section: Discussionmentioning
confidence: 99%
“…Non-CP children with high NSA and HSA at age 3 years old showed a continuous decrease in angles (average decrement in NSA, −1.1°/year [95% CI: −1.5 to −0.8°/year]; in HSA, −1.1°/year [95% CI: −1.5 to − 0.7°/year]). [ 21 ] One study comparing the evolution of the HSA in CP and non-CP children showed that the HSA of non-CP children and ambulatory CP children (GMFCS levels II and III) decreased between 2 and 8 years of age. In contrast, the HSA of nonambulatory children with CP (GMFCS levels IV and V) did not show a decrement as they grew over the same period.…”
Section: Discussionmentioning
confidence: 99%
“…15 Of note, the neck-shaft angle in children does change with age. Van Geel et al 16 investigated the evolution of head-shaft angle (HSA) and neck-shaft angles during childhood. They found a high negative correlation for HSA between the initial measurement and the rate of change over time, indicating that a larger angle during the early years is predictive of a faster decrease in that angle through adolescence.…”
Section: Coxa Valgamentioning
confidence: 99%
“…They found a high negative correlation for HSA between the initial measurement and the rate of change over time, indicating that a larger angle during the early years is predictive of a faster decrease in that angle through adolescence. 16 The mean age of the 286 measurements for 84 different measured hips was 7.4 years (standard deviation [SD]: 2.9). The HSA ranged from 133.8 to 177.8 degrees with a mean of 154.1 degrees (SD: 7.2).…”
Section: Coxa Valgamentioning
confidence: 99%